Javanese cosmology: Symbolic transformation of names in Javanese novels - Pamungkas, Onok Y. (HTS teologiese studies, 2021)
In the past, no research has been found on onomastics from a mystical perspective in literature. This study investigated onomastics in the tetralogy of novels by Ki Padmasusastra (after this referred to as TNKP). The main point of view is the meaning of Javanese cosmology. Qualitative methods are used as research guidelines. The primary data are four Javanese novels. Hermeneutic techniques and content analysis are applied to analytical strategies. The results showed that the onomastics in TNKP are symbols of Javanese cosmology. This element of Javanese cosmology has transformed onomastics through three things: the novel title, figure’s name and location name. The symbolisation of the onomastic is implicit because it is wrapped in the aesthetics of the literary language. The name structure of each onomastic subsection has no clear meaning because the name element is intended for the sense of ‘the other’. Names have an explicit function, namely as hypertextual fragments of symbols that transcend the narrative text structure. An important implication of this investigation is that onomastics can promote the transdisciplinary aspects of religion in international theology in the study of narrative texts. The cosmological transformation of Java can be reflected in various parts of culture, including in novels. TNKP is a cross-disciplinary meeting: fiction, linguistics, mystical, social, cultural and philosophical, contributing to further theological studies.Contribution: This article contributes to the purpose of HTS Teologiese Studies/Theological Studies to promote the transdisciplinary aspects of religious studies in the international theological arena of hermeneutic and philosophical studies behind the narrative text.